MINAT IBU MENGUNJUNGI POSYANDU DIWILAYAH KERJA PUSKESMAS SIMPANG BARU KECAMATAN TAMPAN - Ria Andryana; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The problem of this study showed the factors which influence mother’s interest in visiting Posyandu in Local Clinic Simpang Raru, Tampan. Mother’s interest could be measure through intensity of visiting Posyandu every year. This study used quota sampling technique. The population was all of mothers who have children in Simpang Baru, Tampan at Jalan Uka. The sample was, 30 mothers who always, rare, and never, visiting Posyandu. The data nalysis is descriptive quantitative. The data collection technique are questionnaire and interview.The theory used in this study were interest theory by Hurlock, social action theory by Weber and Health belief model by Rosentock. By this study, it could be concluded that mother’s interest in Reflesia Posyandu in Local Clinic Simpang Baru, Tampan belonged to high percentage, that show 67,7 % mother visited, brought their child to posyandu and thought that posyandu was important. It showed that the mother has good consciousness to visit posyandu. It could be seen when the mother who always visit posyandu more than the mother who rarely visit and never visit. This study also showed that the other factors which influence mother’s interest in visiting posyandu are the distance between the house and posyandu, and their occupation. The distance influenced the mother’s interest that 67,6 % the mother whose house near to posyandu tend to visit posyandu, and the rest is the mother, whose house far away, never visiting posyandu. The most influence factor was kind of mother’s occupation that 73,3 % had unattached occupation was always visiting PosyanduKeywords : Interest, Mother,Posyandu